Development culture, technology and context-based performance assessment model to enhance students’ problem-solving skills - Novianti, Dwi Erna; Zaenuri, Zaenuri; Wardono, Wardono; Sugiman, Sugiman (Edelweiss Applied Science and Technology, 2026)
Problem solving is an approach that bridges mathematical abilities and conceptual understanding. The aims of the current study are the integration of four elements: culture, technology, contextual learning, and performance assessment, which are combined into a single systematic and empirically tested model, namely the CTC-P model. This study employed a research and development (R&D) method. The development stage encompassed three main components: model validation, readability testing, and testing. The study was conducted at a junior high school. The class was selected through random sampling. The research instruments included teaching modules, instructional materials, student worksheets, and a mathematical problem-solving ability test. At the implementation stage, the refined model was disseminated and applied on a large scale using a quasi-experimental design. This design compared students' learning outcomes between an experimental group, which received instruction through the CTC-P model, and a control group, which engaged in conventional learning without intervention. The CTC-P learning model was deemed effective based on three criteria: 1) students are better able to solve math problems using the CTC-P model compared to other models; 2) the classical mastery criterion is achieved, with at least 75% of students scoring above 75; and 3) teachers can effectively implement the CTC-P model.